JEALOUSY IN THE MOVIE THE DEEP BLUE SEA 2011 - Firqo Amelia; Mahrir Wahyuning Sudarminto; Dwi Taurina Mila Wardhani (Lexeme : Journal of Linguistics and Applied Linguistics, 2021)
Jealousy is close to human’s life. Human express it in different levels depending on the cause of the appearance. In this study, jealousy is analysed and exposed in the case of marriage relationship. This study is aimed to find out the cause of the jealousy phenomenon in the movie The Deep Blue Sea. This research used descriptive qualitative method to analyse deeply about jealousy depicted in the movie The Deep Blue Sea. The data analysis technique was taken from Miles ad Huberman’s theory. This psychoanalysis research used the theory of Kingham and Gordon to analyse cause of jealousy. The result showed that jealousy in the movie was caused by locus of causality, controllability and stability. Besides, the affiliation concerning jealousy and protections was considerably sturdier for males than for females. It was defined that a relationship regarding jealousy as well as self-confidence did indisputably be existent, hitherto this was simply the instance for females. For males, jealousy was originated to be essentially associated with practice of defence.